Kepuasan dan Loyalitas Klien di Klinik Hewan Nagasatwa Pet Shop dan Vet Care Pangkalpinang - Yulia Fitriani; Ahmad Yani; Juhari (Jurnal Multidisiplin Borobudur, 2023)
The primary objective of this research is to examine how service quality, facilities, and online marketing impact client satisfaction and, in turn, influence client loyalty at Nagasatwa Pet Shop and Vet Care Animal Clinic in Pangkalpinang. The study's target population comprises clients who have visited the Pangkalpinang Nagasatwa Pet Shop, and a sample of 375 respondents was selected using a qualitative method with a descriptive approach. The researchers employed various data collection techniques, including interviews, direct observation, and the analysis of relevant documents. To analyze the data, regression analysis models, the coefficient of determination test (R2), path analysis (path analysis), the F test (simultaneous), and the t test (partial) were utilized.The research findings indicate that service quality, facilities, and online marketing significantly and positively impact client satisfaction and, consequently, lead to increased client loyalty. The calculated F value of 1056.000 exceeds the F table value of 2.396, with a significance level of 0.000, which is less than the standard significance level of 0.05.